THE RIGHT TO ACCESS BANKING DATA IN A CLAIM FOR A DIVISION OF COMBINED ASSETS THAT IS FILED SEPARATELY FROM A DIVORCE CLAIM - Faizal Kurniawan; Xavier Nugraha; Bagus Oktafian Abrianto; Syifa Ramadhanti (Faculty of Law, Universitas Sebelas Maret, 2020)
Bank Secrecy remains as one of the most essential principles of banking. In Indonesia, however, this principle is not absolute. According to Article 40 (1) of Law No.10 of the Year 1998 regarding changes to Law Number 7 of the Year 1992 regarding Banking alongside Article 2 (4) of Bank Indonesia Number : 2/19/PBI/2000 regarding several exceptions in implementing Bank Secrecy. In its implementation, these exceptions have yet to adjust to recent social development. One problematic case is when it relates to a claim of combined assets that is filed in conjunction with a claim for divorce. In recent development, the Constitutional Court has asserted that the one of the exceptions for Bank Secrecy can occur for cases of divorce, in its Judgement Number 64/PUU-X/2012. However, this decision has yet to answer a problematic issue when the claim for divorce is filed separately from the claim for the division of combined assets. Such decision does not consider cases in which the two aforementioned claims are filed separately. This presents a problem for couples who are not muslim and are confined to divorce laws in which the two claims must be filed separately. Thus, does a claim for the division of combined assets that is filed separately from the claim of divorce fall under the Scope of Constitutional Court Decision Number 64/PUU-X/2012? According to the following research, such cases indeed fall under the scope of Constitutional Court Decision Number 64/PUU-X/2012. This conclusion is based on historical interpretation and Extensive Interpretation. According to historical interpretation, the original intent of the judges in drafting Constitutional Court Decision Number 64/PUU-X/2012 is to provide both the husband/wife equal share of their wealth. According to extensive interpretation, the concept of filing both claims separately is to an extension of the concept explicitly addressed in such Constitutional Court decision.